Furan-based self-healing breathable elastomer coating on polylactide fabric. Issue 5 (March 2019) - Ryu, Yeon Sung; Oh, Kyung Wha; Kim, Seong Hun
The demand for breathable waterproof products has increased with the need for functional sportswear. However, these membranes have a major weakness in the loss of performance over time. The self-healing polymer has attracted much attention as a solution to this problem. In this research, a bio-based self-healing polymer from furan-based polymer was synthesized to produce a sustainable waterproof membrane. The furan-based self-healing polymer was synthesized from poly(butylene furanoate) and bismaleimide via a Diels–Alder reaction and blended with bio polyurethane. Poly(ethylene glycol) was also blended to obtain nonporous breathable waterproofness. These synthesis processes were identified by spectroscopy analysis. To investigate the self-healing ability of the polymer, a film sample was sliced and reattached. These self-healing processes were observed and verified by morphological and mechanical analysis. These self-healing polymer films were successfully healed in 24 h. The polymer was coated on a polylactide fabric using a doctor blade. The self-healing ability of the membrane was investigated by breathable water repellency analysis and it was maintained after the coating process. The waterproofness and vapor permeability were also measured, and these results identified that the fabricated membrane has a possibility as a breathable waterproof fabric. Environmental performance was confirmed by the enzymatic degradation test.